Retorno à atividade reprodutiva de touro angus após fimose traumática com obliteração parcial da luz prepucial: relato de caso - Silva, Luis Fernando Mercês Chaves [UNESP]; Araujo, Endrigo Adonis Braga de [UNESP]; Oliveira, Sidnei Nunes de [UNESP]; Dalanezi, Felipe Morales [UNESP]; Zahn, Fabíola Soares [UNESP]; Papa, Frederico Ozanam [UNESP] (My University, 2015)
The main disturbs affecting the genital segment of bulls are balanitis, phimosis and preputial injuries, abscesses or prolapses, resulting in decreased libido or mating ability. One case of traumatic phimosis with partial obliteration of preputial lumen is reported in Aberdeen Angus bull. During anamnesis, it was reported that the animal was unable to expose the penis and presented increased penile and preputial volume of unknown etiology after being submitted to a libido test. During clinical examination, a firm preputial mass of 15 cm in diameter was observed in the middle third of the prepuce and stenosis of preputial lumen was detected approximately 17 cm from the preputial orifice. Reconstructive surgery was the chosen therapy, with amputation of the affected foreskin portion. A skin segment of about 12 cm and affected mucosal portion were removed. Postoperative therapy consisted of dressing with chlorhexidine digluconate based ointment, povidone iodine and topical insect repellent (cypermethrin and carbamyl), systemic antibiotic therapy with benzathine penicillin (30,000 IU / kg, repeated after 48 hours) and anti-inflammatory therapy with flunixin meglumine (2 , 0 mg / kg SID) for three days. After twenty days, semen was collected by massage of the accessory glands. The ejaculate volume was 3 mL, with 200x106 spermatozoa / mL, white color, "suis generis" odor, 88% of motile sperm, 64% of progressively motile sperm and 82% of rapid sperm. Thus, the chosen surgical treatment was effective to correct the pathology and reintroduce the animal into reproductive activity

As principais patologias que afetam o segmento genital dos touros são as balanites, as acrobustites, abcessos prepuciais, prolapso e fimose, resultando em perda da libido ou da capacidade de copular. Relata-se um caso de fimose traumática com obliteração parcial da luz prepucial em touro da raça Aberdeen Angus. À anamnese, revelou-se que, após realizar um teste de libido, o animal demonstrou incapacidade de exposição do pênis e aumento de volume prepucial de etiologia desconhecida. Ao exame clínico, detectou-se aumento de volume de 15cm de diâmetro no terço médio do prepúcio, com consistência firme à palpação e estenose da luz prepucial a aproximadamente 17 cm do óstio prepucial. O tratamento eleito foi a realização de cirurgia reparadora, com amputação da porção prepucial acometida. Promoveu-se, então, a remoção do segmento com cerca de 12 cm de mucosa e da porção estenosada. O pós-operatório consistiu de curativo com pomada a base de digluconato de clorexidina, iodo povidine tópico e repelente de insetos (cipermetrina e carbamil), antibioticoterapia sistêmica com penicilina benzatina (30.000 UI/kg, repetida após 48 horas) e terapia anti-inflamatória com flunixin meglumine (2,0 mg/Kg SID) por três dias. Após vinte dias, realizou-se colheita de sêmen por massagem das glândulas anexas. O volume ejaculado foi de 3 mL, com 200x106 espermatozoides/mL, cor branca e odor “suis generis”, 88% de células móveis, 64% de motilidade progressiva e 82% de espermatozoides rápidos. Desta forma, o tratamento cirúrgico realizado mostrou-se eficiente para corrigir a patologia reintroduzindo o animal à atividade reprodutiva
Recovery of angus bull after traumatic phimosis with partial obliteration of the preputial lumen: case report
Keywords: Bull; Preputial disturbs; Coeundi impotence; Reconstructive surgery; Afecções prepuciais; Cirurgia corretiva; Impotência coeundi; Touro